Detection of submicroscopic infection with Plasmodium spp., using classical and molecular techniques in pregnant patients from Córdoba, Colombia (2014)
Introduction: Gestational malaria affects both the mother and the development of her embryo or fetus. Rapid diagnosis and timely and effective treatment are required to prevent complications and deaths. Objective: To compare thick blood smear with nested PCR and real-time PCR (qRT-PCR) for the diagnosis of submicroscopic infections with Plasmodium falciparum and P. vivax. Methodology: 21 women with clinical manifestations of malaria, including both pregnant and non-pregnant, were studied in Puerto Libertador, Córdoba, Colombia. Peripheral blood specimens were obtained from all of them; umbilical cord and placenta blood specimens were taken in the pregnant ones. DNA was extracted and amplified for nested PCR or qRT-PCR. Statistical analysis was done using Graphpad PRISM and EPIDAT softwares. Results: The three techniques were satisfactory for the detection of Plasmodium falciparum and P. vivax in peripheral blood and in the umbilical cord and placenta specimens. Molecular tests were 100% sensitive and specific. Two submicroscopic cases of P. falciparum infection were detected with the two PCR techniques. Conclusion: qRT-PCR is advantageous over nested PCR because its standardization is shorter, it requires lesser infrastructure and it allows the quantification of DNA.